A2A Receptor Contributes to Tumor Progression in P2X7 Null Mice - De Marchi, Elena; Pegoraro, Anna; Turiello, Roberta; Di Virgilio, Francesco; Morello, Silvana; Adinolfi, Elena (Frontiers in Cell and Developmental Biology, 2022)
ATP and adenosine are key constituents of the tumor niche where they exert opposite and complementary roles. ATP promotes tumor growth but also immune eradicating responses mainly via the P2X7 receptor (P2X7R), while adenosine acts as a potent immune suppressor and facilitates neovascularization thanks to A2A receptor (A2AR) activity. However, studies exploring the interplay between P2X7R and A2AR in the tumor microenvironment are as yet missing. Here we investigated tumor growth in C57/bl6 P2X7 null mice inoculated with B16-F10 melanoma cells, showing that several pro-inflammatory cytokines (IL1-β, TNF-α, IL-6, IL-12, IL-17, IFN-γ) were significantly decreased while the immune suppressant TGF-β was almost three-fold increased. Interestingly, tumors growing in P2X7-null mice also upregulated tumor-associated and splenic A2AR, suggesting that immunosuppression associated to lack of the P2X7R might depend upon A2AR overexpression. Immunohistochemical analysis showed that tumor cells A2AR expression was increased, especially around necrotic areas, and that VEGF and the endothelial marker CD31 were also upregulated. The A2AR antagonist SCH-58261 reduced tumor growth similarly in the P2X7 WT, or null mice strain. However, SCH-58261only reduced VEGF in the P2X7-KO mice, thus supporting the hypothesis of an A2AR mediated increase in vascularisation in P2X7-null host. SCH-58261 administration also significantly reduced intratumor TGF-β, thus supporting a key immune suppressive role of A2AR in our model. This study shows a novel direct correlation between P2X7R and A2AR in oncogenesis and paves the way for new combined therapies promoting anti-cancer immune responses and reducing tumor vascularization.